Chaperome screening leads to identification of Grp94/Gp96 and FKBP4/52 as modulators of the α‐synuclein‐elicited immune response. Issue 2 (6th October 2015) - Labrador‐Garrido, Adahir; Cejudo‐Guillén, Marta; Daturpalli, Soumya; Leal, María M.; Klippstein, Rebecca; De Genst, Erwin J.; Villadiego, Javier; Toledo‐Aral, Juan J.; Dobson, Christopher M.; Jackson, Sophie E.; Pozo, David; Roodveldt, Cintia
Abstract : We have investigated the potential role of molecular chaperones as modulators of the immune response by using α‐synuclein (αSyn) as an aggregation‐prone model protein. We first performed an in vitro immunoscreening with 21 preselected candidate chaperones and selected 2 from this set as displaying immunological activity with differential profiles, Grp94/Gp96 and FKBP4/52. We then immunized mice with both chaperone/α‐synuclein combinations using monomeric or oligomeric α‐synuclein (MαSyn or OαSyn, respectively), and we characterized the immune response generated in each case. We found that Grp94 promoted αSyn‐specific T‐helper (Th )1/Th 17 and IgG1 antibody responses (up to a 3‐fold increase) with MαSyn and OαSyn, respectively, coupled to a Th 2‐type general phenotype (generating 2.5‐fold higher IgG1/IgG2 levels). In addition, we observed that FKBP4 favored a Th 1‐skewed phenotype with MαSyn but strongly supported a Th 2‐type phenotype with OαSyn (with a 3‐fold higher IL‐10/IFN‐γ serum levels). Importantly, results from adoptive transfer of splenocytes from immunized animals in a Parkinson's disease mouse model indicates that these effects are robust, stable in time, and physiologically relevant. Taken together, Grp94 and FKBP4 are able to generate differential immune responses to α‐synuclein‐based immunizations, depending both on the nature of the chaperone and on the aggregation state of α‐synuclein. Our work reveals that several chaperones are potential modulators of the immune response and suggests that different chaperones could be exploited to redirect the amyloid‐elicited immunity both for basic studies of the immunological processes associated with neurodegeneration and for immunotherapy of pathologies associated with protein misfolding and aggregation.—Labrador‐Garrido, A., Cejudo‐Guillen, M., Daturpalli, S., Leal, M. M., Klippstein, R., De Genst, E. J., Villadiego, J., Toledo‐Aral, J. J., Dobson, C. M., Jackson, S. E., Pozo, D., Roodveldt, C. Chaperome screening leads to identification of Grp94/Gp96 and FKBP4/52 as modulators of the α‐synuclein‐elicited immune response. FASEB J. 30, 564‐577 (2016). www.fasebj.org